Quando l'autore corregge se stesso. Il caso unico del copialettere di Francesco Guicciardini (Quaderni di Gargnano, 2018)
Francesco Guicciardini’s letterbook is a unique among the records left by the historian. It contains a large number of letters to and from Guicciardini from the years 1526-1527 that were faithfully copied down by the Guicciardini’s secretary-scribe in a volume which has since been broken up but whose codicologically coherent parts can be traced back to the same original source. The paper investigates how the letterbook was compiled by comparing the letters it includes with other samples (drafts, originals) of the same documents.
Keywords: Carteggio; Francesco Guicciardini; copialettere; codicologia